PERGESERAN BAHASA INDONESIA DALAM PENGGUNAAN RAGAM GAUL PADA KOMUNIKASI SISWA SMA NEGERI 8 MAKASSAR: INDONESIAN LANGUAGE SHIFT IN THE USE OF SLAGING VARIETIES IN STUDENT COMMUNICATION AT STATE SENIOR HIGH SCHOOL 8 MAKASSAR - Rahmi, Nasyrah; Saleh, Muhammad; Baharman (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
This study aims to reveal the form and influence of slang variety on the shift of Indonesian language in the communication of students of SMA Negeri 8 Makassar. describe the factors that cause the shift of Indonesian language of SMA Negeri 8 Makassar students. This research uses a descriptive qualitative approach, the data sources of this research are conversations and student interview results. The form of data in this research is phrases and sentences in slang used by students in communicating in the school environment. Data collection techniques in this research are observation and interview techniques. The data analysis technique in this research uses Miles and Huberman data analysis, namely data collection, data reduction, data presentation, and conclusion drawing. The results showed that (1) the influence of slang variety on Indonesian language shifts in student communication is seen from changes in the structure of phonology, morphology, syntax, and lexicon, which are manifested in 8 forms, namely, pronouns, acronyms, abbreviations, absorption, shortening, inversion, new words, and improvisation of the original word. (2) The factors that cause Indonesian language shift in the communication of SMA Negeri 8 Makassar students are social environment, culture, technological development and social media.